MISTISISME DAN HAL-HAL TAK TERCAKAPKAN: MENIMBANG EPISTEMOLOGI HUDHÅªRÄª - Sabri, Muhammad (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
In general, this article intends to answer a fundamental question, whether a mystical experience can or cannot be expressed through language. If the answer is positive, what kind of language can â€˜formulateâ€™ an inner space of human experienceto penetrateinto the heart of the most real reality? What kind of consciousness can â€œbringâ€ the light of God to the â€˜empiricalâ€™ world Then how to formulate a mystical consciousness in expressing spiritual experience that is â€œsubjectiveâ€ and therefore, has limitations? How, in fact, the status of â€œnon-subjective phenomenalâ€ consciousness in Islamic epistemology? The above questions, of course, are just a small ripple for those who seek to dive into the depth of â€œMystical Ocean without shoreâ€. To give an answer, this article then presents two contemporary philosophers from the genre of analytic philosophy, but from a diff erent background from that of tradition: Ludwig Wittgenstein (1889-1951) and Mehdi Haâ€™iri Yazdi (1923 to 1999). This article appears to be a â€œresistanceâ€ epistemic: to show the fragile philosophical structure of positivism to capture the invisible â€˜realitiesâ€™. This last genre of philosophy, which is concerned mostly with thereliability of facts, the necessity correspondence between the facts and language, and glorifi es the verifi cation principles, has experienced â€œstuttersâ€ in every endeavor to reveal the world of meaning. h is article, also seeks reveal the way to the world of â€œexperienceâ€ and does not stop at the world of knowledge. By adopting the approach of Analytic Philosophy, this article shows the folds of meaning and reality: empirical, meta-empirical, existential, and spiritual. For the author, the all layers of reality can only be revealed through a mysticalexperience, a presential knowledge (al-â€™ilm al-hudhÅ«rÄ«) in a perfect ontological state